KREATIVITAS GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMKN 2 PARIAMAN - Novebri, Novebri (UIN Imam Bonjol Padang, 2021)
This study aims to investigate the teacher creativity in SMKN 2 Pariaman. The study utilized quantitative method with descriptive approach. The population in this study are all of teachers in SMKN 2 Pariaman, they are 102 teachers and sample of this study is 53 teachers with stratified proportional random sampling technique. The data were analyzed by using analysis technique though SPSS 20.0. The result found that (1) teacher creativity based on open minded feature with mean score 3,94 at high category, (2) teacher creativity based on problem solving feature with mean score 4,15, at high category (3) teacher creativity based on humorous feature with mean score 3,83 at high category and (4) teacher creativity based on innovative feature with mean score 3,64 at high category. Therefore, the conclusion was teacher creativity in SMKN 2 Pariaman is at high category level and it can increase learning quality.